Analisis Pemanfaatan Teknologi Digital dalam Pemeliharaan Sistem Tenaga Listrik: Literature Review terhadap Implementasi Predictive Maintenance - Fiana Fiana; Ardian Nurarifin; Muhamad Taufiq Hidayatullah Syari; Muhamad Rifki Arrosyid; Didik Aribowo (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
The rapid advancement of digital technologies has transformed maintenance practices in electric power systems, encouraging a shift from conventional approaches toward predictive maintenance strategies. This study examines the role of digital technologies in supporting predictive maintenance through a comprehensive literature review. The research was conducted by analyzing scientific journals, conference papers, and scholarly articles discussing the application of Internet of Things (IoT), Artificial Intelligence (AI), machine learning, SCADA, and digital twin technologies in power system maintenance. The review indicates that predictive maintenance contributes to improved system reliability, reduced equipment downtime, lower maintenance expenditures, and enhanced operational efficiency through continuous monitoring and data-based decision making. Furthermore, digital technologies facilitate earlier fault identification and more effective maintenance scheduling. Despite these benefits, several challenges remain, including cybersecurity concerns, investment requirements for digital infrastructure, and the need for skilled personnel. The findings of this study provide insights that may support the development of more intelligent, efficient, and reliable power systems in the future.